Analisis Pengelolaan Persediaan Barang Box Polyurethane Berbasis Standar World Health Organization Di PT Bio Farma (Persero) - Pratiwie Nirmala Dewi; Chandra Hendriyani (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
Changes in lifestyle and human interaction are now one of the drivers of the emergence of various diseases in the world. The current global pandemic is Coronavirus (Covid-19) is a pandemic that occurred in Wuhan China involving humans who like to eat wild animals that are sold at the Wuhan animal market. The existence of the pharmaceutical industry is one of the needs that can also become a financial driver of a country, including in Indonesia. PT Bio Farma (Persero) is a state-owned company that manufactures international quality vaccines and anti sera. PT Bio Farma (Persero) is the only vaccine manufacturer for humans in Indonesia and the largest in Southeast Asia and already has qualification standards from WHO (World Health Organization). To meet the standardization as a WHO global player, PT Bio Farma (Persero) maintains the vaccine quality standards it produces from the initial manufacturing process to the final vaccine delivery process. One of the processes in the series of stages is the process of managing inventory. One of the items that is often imported from vendors to PT Bio Farma (Persero) for the continuity of the company's production activities is the Polyurethane Box. This box functions to keep the vaccine sterile until it reaches the customer. The purpose of this research is to study how the process of managing goods inventory of Box Polyurethane from receipt of goods to storage in warehouses with standards set by WHO. The research method used is descriptive discussion. Data collection techniques were carried out by observation, interviews with branch unit secretaries, and literature studies from books, journals, and documents related to research discussions.